Loading jsMath...



Algebra

Analyse

Bewijzen

De grafische rekenmachine

Discrete wiskunde

Fundamenten

Meetkunde

Oppervlakte en inhoud

Rekenen

Schoolwiskunde

Statistiek en kansrekenen

Telproblemen

Toegepaste wiskunde

Van alles en nog wat


\require{AMSmath}

5. Quotiëntregel

\eqalign{   & Als\,\,f(x) = \frac{{g(x)}} {{h(x)}}\,\,dan:  \cr   & f'(x) = \frac{{g'(x) \cdot h(x) - g(x) \cdot h'(x)}} {{\left( {h(x)} \right)^2 }} \cr}

Voorbeeld 1

\eqalign{   & Als\,\,f(x) = \frac{{2x}} {{x^2  - 2}}\,\,dan:  \cr   & f'(x) = \frac{{2 \cdot \left( {x^2  - 2} \right) - 2x \cdot 2x}} {{\left( {x^2  - 2} \right)^2 }}  \cr   & f'(x) = \frac{{2x^2  - 4 - 4x^2 }} {{\left( {x^2  - 2} \right)^2 }}  \cr   & f'(x) = \frac{{ - 2x^2  - 4}} {{\left( {x^2  - 2} \right)^2 }} \cr}

Voorbeeld 2

\eqalign{   & f(t) = \frac{{1 - 3t - 3t^2 }} {{3t^2  - 2t^3 }}  \cr   & f'(t) = \frac{{\left( { - 3 - 6t} \right)\left( {3t^2  - 2t^3 } \right) - \left( {1 - 3t - 3t^2 } \right)\left( {6t - 6t^2 } \right)}} {{\left( {3t^2  - 2t^3 } \right)^2 }}  \cr   & f'(t) = ... \cr}

Voorbeeld 3

\eqalign{   & f(x) = \frac{x} {{\left( {2x - 1} \right)^2 }}  \cr   & f'(x) = \frac{{1 \cdot \left( {2x - 1} \right)^2  - x \cdot 2\left( {2x - 1} \right) \cdot 2}} {{\left( {\left( {2x - 1} \right)^2 } \right)^2 }}  \cr   & f'(x) = \frac{{\left( {2x - 1} \right)^2  - 4x\left( {2x - 1} \right)}} {{\left( {\left( {2x - 1} \right)^2 } \right)^2 }}  \cr   & f'(x) = \frac{{2x - 1 - 4x}} {{\left( {2x - 1} \right)^3 }}  \cr   & f'(x) = \frac{{ - 2x - 1}} {{\left( {2x - 1} \right)^3 }}  \cr   & f'(x) = \frac{{2x + 1}} {{\left( {1 - 2x} \right)^3 }} \cr}

Voorbeeld 4

\eqalign{   & f(x) = 12 \cdot \frac{{\left( {x^2  - 1} \right)}} {{x^2  + 12}}  \cr   & f'(x) = 12 \cdot \frac{{\left[ {\left( {x^2  - 1} \right)} \right]^|  \cdot \left( {x^2  + 12} \right) - \left( {x^2  - 1} \right) \cdot \left[ {x^2  + 12} \right]^| }} {{\left( {x^2  + 12} \right)^2 }}  \cr   & f'(x) = 12 \cdot \frac{{2x \cdot \left( {x^2  + 12} \right) - \left( {x^2  - 1} \right) \cdot 2x}} {{\left( {x^2  + 12} \right)^2 }}  \cr   & f'(x) = 12 \cdot \frac{{2x\left\{ {\left( {x^2  + 12} \right) - \left( {x^2  - 1} \right)} \right\}}} {{\left( {x^2  + 12} \right)^2 }}  \cr   & f'(x) = 12 \cdot \frac{{2x\left\{ {x^2  + 12 - x^2  + 1} \right\}}} {{\left( {x^2  + 12} \right)^2 }}  \cr   & f'(x) = 12 \cdot \frac{{2x \cdot 13}} {{\left( {x^2  + 12} \right)^2 }}  \cr   & f'(x) = \frac{{312x}} {{\left( {x^2  + 12} \right)^2 }} \cr}

Voorbeeld 5

\eqalign{   & f(x) = \frac{{a^2  - x^2 }} {{a^2  + x^2 }}  \cr   & f'(x) = \frac{{ - 2x\left( {a^2  + x^2 } \right) - \left\{ {\left( {a^2  - x^2 } \right) \cdot 2x} \right\}}} {{\left( {a^2  + x^2 } \right)^2 }}  \cr   & f'(x) = \frac{{ - 2a^2 x - 2x^3  - \left\{ {2a^2 x - 2x^3 } \right\}}} {{\left( {a^2  + x^2 } \right)^2 }}  \cr   & f'(x) = \frac{{ - 2a^2 x - 2x^3  - 2a^2 x + 2x^3 }} {{\left( {a^2  + x^2 } \right)^2 }}  \cr   & f'(x) = \frac{{ - 4a^2 x}} {{\left( {a^2  + x^2 } \right)^2 }} \cr}

F.A.Q.



©2004-2025 WisFaq